A virtue ethics framework for modern anatomical pathology - Miniggio, Hilde Doris (My University, 2022)
The central aim in this thesis is to develop a nuanced and practicable virtue ethics framework for modern anatomical pathology. The development of this framework is motivated by the neglect of virtue concepts in the current ethics discourse pertaining to modern anatomical pathology, coupled with the gaps associated in the application of the commonly used principlebased approach, in addressing ethical issues specifically encountered in the routine practice of modern anatomical pathology. This thesis addresses the gaps in current literature by advancing a virtue ethics framework for a neglected healthcare practice. The aim of this framework is to redirect the focus of ethical decision-making on the human facets, unique relationships and role-specific responsibilities characteristic of the practice. Furthermore, the virtue ethics framework is intended to guide ethical decision-making in the context of modern anatomical pathology practice, promote excellence in the achievement of the internal goods and immediate ends specific to the practice which in turn, furthers its telos, the well-being of the patient. Lastly, this framework aims to serve as the initial basis for the development of virtuous anatomical pathologists, through virtue-based moral education. In outline, modern anatomical pathology is a diagnostic speciality that is largely laboratory based and that has progressively lost direct contact with the patients that they treat by means of a pathological diagnosis. Being laboratory based, however, does not mean that anatomical pathologists are not involved in patient care. In fact, advances in molecular diagnostic techniques are facilitating the involvement of the modern anatomical pathologist in caring for patients beyond the classical one-time diagnosis to a more elaborate involvement as part of the personalised approach to modern healthcare provision. The thesis is structured as follows. Chapter one is the introductory chapter which provides the rationale for the thesis coupled with a brief overview of the various chapters and contributions made to the field. Chapter two characterises the various technical and human tasks that are involved in the pathological diagnostic process, that informs the ethical debates in subsequent chapters. Chapter three is a critical analysis of the shortcomings of the principle-based approach in resolving ethical conflicts that arise in clinical healthcare provision in general, and specifically, in modern anatomical pathology practice. In chapter four, I evaluate whether a virtue-based approach is suitable in bridging the gaps identified in the application of the principle-based approach in the context of modern anatomical pathology practice and claim that it is. Thereafter, in chapter five, I discuss the noteworthy elements of a couple of virtue accounts, specifically developed for clinical healthcare provision and pathology, respectively. In the latter part of chapter five, I present the initial elements of my virtue ethics framework in which I propose the use of empirical research in addition to philosophical analysis for the development of a comprehensive and practical framework. Chapter six is concerned with the presentation of the empirical findings in this thesis which informs the construction of the virtue ethics framework in chapter seven and the assessment of the ethical issues characteristic to the practice of modern anatomical pathology, in light of the framework developed in this thesis. My conclusion is that the proposed framework is cogent, nuanced, and useful in application to resolving ethical issues that arise in the context of modern anatomical pathology practice with a view of shaping and encouraging the development of professional virtues which ensures virtuous practice.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy (Bioethics and Health Law) to the Faculty of Health Sciences, School of Clinical Medicine, University of Witwatersrand, Johannesburg, 2022